New insight into the molecular mechanism of miR482/2118 during plant resistance to pathogens - Liao, Lijuan; Xie, Biao; Guan, Peipei; Jiang, Ning; Cui, Jun (Frontiers in Plant Science, 2022)
MicroRNAs (miRNAs), a group of small noncoding RNAs (approximately 20-24 nucleotides), act as essential regulators affecting endogenous gene expression in plants. MiR482/2118 is a unique miRNA superfamily in plants and represses NUCLEOTIDE BINDING SITE-LEUCINE-RICH REPEAT (NBS-LRR) genes to function in plant resistance to pathogens. In addition, over the past several years, it has been found that miR482/2118 not only targets NBS-LRRs but also acts on other molecular mechanisms to affect plant resistance. miR482/2118-5ps, phased small interfering RNAs (phasiRNAs) and long noncoding RNAs (lncRNAs) play important roles in plant disease resistance. This review summarizes the current knowledge of the interactions and links between miR482/2118 and its new interacting molecules, miR482/2118-5p, phasiRNAs and lncRNAs, in plant disease resistance. Here, we aim to provide a comprehensive view describing the new molecular mechanism associated with miR482/2118 in the plant immune system.